Computer controlled hydraulic bulging machine - Thiruvarudchelvan, Sinnathamby (2008)
A hydraulic bulging machine with independent pressure and axial force control has been designed and constructed. A personal computer together with a data logger was used to control the internal hydraulic pressure, the axial load, compression of the tube and the operating sequence of the process. A theoretical study of the tube bulging process has also been conducted Results of the bulging experiments conducted with this set up are reported.